PERSPEKTIF INTEGRASI INTERKONEKSI BOLA SALJU LONJAKAN PESANTREN DAN PENGKERDILAN SEKOLAH UMUM DALAM PETA JALAN PENDIDIKAN INDONESIA - Azlina; Haris Riadi; Marlizayani; Azizah; Rahmad (Institut Agama Islam Hamzanwadi NW Lombok Timur, 2025)
This study aims to examine the phenomenon of integration-interconnection in the context of the increasing popularity of Islamic boarding schools and the marginalization of public schools in Indonesia. Islamic boarding schools, which are increasingly in demand as religious-based education, are faced with public schools that face the challenge of relevance amidst global competition. The main problem of this study is the tension between the two educational systems and the potential of the concept of integration-interconnection to create harmonious synergy. Library research method with a descriptive-analytical approach. Data were collected from various literatures, such as books, scientific journals, and policy documents, then analyzed using content analysis techniques. This study identifies challenges, opportunities, and solutions in implementing integration-interconnection. The results of the study indicate that integration-interconnection can be a strategic solution to address educational challenges in Indonesia. The main findings include the need for curriculum renewal, improving the competence of teaching staff, and changing the paradigm of society to accommodate the synergy between Islamic values ​​and modern science. In conclusion, integration-interconnection is not just a theoretical concept, but a strategic need to create inclusive education that is relevant to global challenges and oriented towards the harmony of religious values ​​and modernity.